Capital Structure Choice: Macroeconomic Conditions and Financial Constraints. (WorkingPaper # 279, Forthcoming Journal of Financial Economics, 2002) - Prasetyowati, Riris Aishah (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2015)
The empirical literature provides conflicting assessments about how firms choose their capital structures. Distinguishing among the three main hypotheses (‘‘tradeoff'', pecking order, and market timing) requires that we know whether firms have long-run leverage targets and (if so) how quickly they adjust toward them. Yet many previous researchers have applied empirical specifications that fail to recognize the potential for incomplete adjustment. A more general, partial-adjustment model of firm leverage indicates that firms do have target capital structures. The typical firm closes about one-third of the gap between its actual and its target debt ratios each year.